Evaluation of Chromosome 11p Imbalances in Aniridia and Wilms Tumor Patients. Issue 5 (13th March 2013) - Busch, Maike; Leube, Barbara; Thiel, Anne; Schanze, Ina; Beier, Manfred; Royer‐Pokora, Brigitte
Abstract Newborn sporadic aniridia patients with an 11p13 deletion including the WT1 gene have an increased risk to develop Wilms tumor. At present a risk for Wilms tumor cannot be estimated in patients with deletions not extending into, but ending close to WT1. Therefore, it is important to determine the distance of deletion endpoints from the WT1 gene and survey these patients for a longer follow‐up time to obtain a more defined risk estimation. Using molecular methods, such as Multiplex Ligation‐dependent Probe Amplification (MLPA), deletion endpoints can be mapped more accurately than with FISH. We describe here the analysis of six aniridia patients, in two of these the deletions extend close to the 3′ end of WT1. At the ages of 3.8 and 4 years they have not developed a Wilms tumor, suggesting a low tumor risk in such patients. In addition we have studied 24 non‐AN cases with a higher likelihood for WT1 alterations with MLPA and found no deletions. In conclusion newborns with aniridia should be studied with molecular methods that can determine deletion endpoints in 11p13 exactly. For a better Wilms tumor risk estimation cases with deletion endpoints close to WT1 should be followed for at least 4–5 years. Furthermore germ line intragenic deletions affecting WT1 in patients with a higher likelihood for a WT1 association, for example, bilateral tumors, genitourinary aberrations, or nephrotic syndrome, were not found in this study, suggesting that deletions are rare events. © 2013 Wiley Periodicals, Inc.